A French man amongst the Murcian booksellers in the18th century - García Cuadrado, Amparo (Revista General de Información y Documentación, 2015)
This article aims to make known the biographical and professional keys of Francisco Fache, a French bookseller established in Murcia. In particular, his activity selling books, published abroad and obtained through its trade relations with Lyon, Marseille and Valencia, as an aspect of its activities as a merchant of books from the mid eighteenth century. This article also approaches to the difficulties experienced with maritime perils in order to supply printed material and seizure of copies, the ruin of business and the application of "expected demand", as well as the pricing of libraries and purchase of old libraries. The notary’s protocol analysis confirms the inclusion of Murcia in European book trade circuits.
Keywords: 18th century; Book trade; Bookselling in Murcia; Expected demand; Francisco Fache; French booksellers; Maritime trade; Murcia.